Cryptococcal meningitis presenting as sinusitis in a renal transplant recipient. Issue 5 (27th August 2013) - Iyer, S.P.; Movva, K.; Wiebel, M.; Chandrasekar, P.; Alangaden, G.; Carron, M.; Tranchida, P.; Revankar, S.G.
Abstract Cryptococcal meningitis is a relatively common invasive fungal infection in immunocompromised patients, especially in solid organ transplant recipients. Clinical presentation typically includes fever, headache, photophobia, neck stiffness, and/or altered mental status. Unusual presentations may delay diagnosis. Therapy is challenging in renal transplant patients because of the nephrotoxicity associated with amphotericin B, the recommended treatment. We present a case of cryptococcal meningitis in a renal transplant recipient presenting as acute sinusitis with successful treatment using fluconazole as primary therapy.